Amine‐Promoted Asymmetric (4+2) Annulations for the Enantioselective Synthesis of Tetrahydropyridines: A Traceless and Recoverable Auxiliary Strategy1. Issue 20 (9th April 2013) - Hu, Pengfei; Hu, Jian; Jiao, Jiajun; Tong, Xiaofeng
<x xml:space="preserve">Abstract</x> Gone, without a trace: The in situ reaction of 2‐(acetoxymethyl)buta‐2, 3‐dienoate and a secondary amine produces a 2‐methylene‐3‐oxobutanoate equivalent that can be used in asymmetric [4+2] annulations with N‐tosylimines to provide tetrahydropyridines in good to excellent yields and enantioselectivities. The amine is easily recovered and acts as a traceless auxiliary.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>